1980
DOI: 10.1149/1.2129944
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and Kinetics of Chemical Vapor Deposition of Aluminum Nitride Films

Abstract: The thermodynamics of aluminum nitride formation in the AlCl3‐NH3‐H2 and AlBr3‐NH3‐H2 systems have been studied at 1200° and 1400°K. The nature of the condensed phase and the equilibrium gas phase composition have been determined. Aluminum nitride was the only condensed phase formed under the entire range of the gas phase composition investigated. With a gas phase composition in stoichiometric proportions false(PAlX30=PNH30false) , the yield of aluminum nitride decreased rapidly when the halide or ammonia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…The CVD A1N plates prepared at Td~p > 1173K had a stoichiometric composition independent of NH3/A1C13 and Ptot. No known reports on the impurity chlorine analysis for CVD A1N are available; however, Pauleau et al [12] examined impurity bromine using the Rutherford back-scattering (RBS) method for the CVD AIN films prepared from the A1Bra + NH3 system. According to Pauleau et al [12], the bromine content in the deposits prepared at Td~p = 723K was about 5 X 1016 atoms cm -2 and decreased with increasing Tdop.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CVD A1N plates prepared at Td~p > 1173K had a stoichiometric composition independent of NH3/A1C13 and Ptot. No known reports on the impurity chlorine analysis for CVD A1N are available; however, Pauleau et al [12] examined impurity bromine using the Rutherford back-scattering (RBS) method for the CVD AIN films prepared from the A1Bra + NH3 system. According to Pauleau et al [12], the bromine content in the deposits prepared at Td~p = 723K was about 5 X 1016 atoms cm -2 and decreased with increasing Tdop.…”
Section: Resultsmentioning
confidence: 99%
“…No known reports on the impurity chlorine analysis for CVD A1N are available; however, Pauleau et al [12] examined impurity bromine using the Rutherford back-scattering (RBS) method for the CVD AIN films prepared from the A1Bra + NH3 system. According to Pauleau et al [12], the bromine content in the deposits prepared at Td~p = 723K was about 5 X 1016 atoms cm -2 and decreased with increasing Tdop. No bromine atoms were detected in deposits prepared above Tdep = 923 K. This trend is in agreement with the present results.…”
Section: Resultsmentioning
confidence: 99%
“…High thermal conductivity, large energy gap, good thermal stability, and chemical inertness of aluminum nitride make it an advanced ceramic material and a suitable dielectric for semiconductor devices. Organoaluminium compounds have been used as precursors for aluminum nitride; however, the product formed has a high degree of carbon contamination due to pyrolysis of the organic substituents and is not suitable for commercial use. The CVD of aluminum chloride and ammonia is well studied and yields high purity AlN. , Despite the fact that this process has been the subject of numerous experimental studies, the chemical nature of the intermediates in AlN growth is still unknown. It has been shown that, together with formation of AlN films, some particles are formed in the gas phase .…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that aluminium Al m (m = 11, 13) clusters are stable and their geometry was computed recently. [47] Probably, (i) the structure of aluminium nitride Al 11 N n (n = 4, 6, 10, 12, 19, 21, 23 and 25) and Al 13 N n (n = 31-36) clusters has a core of Al 11 and Al 13 clusters with nitrogen bound to the cluster surface or (ii) Al 11 N n and Al 13 N n clusters are just fragments formed by laser action from the aluminium nitride crystal structure.…”
Section: Ldi Of Aln Nano-powdermentioning
confidence: 99%
“…[10] AlN ceramics can be produced by different methods; e.g. they can be fabricated by chemical vapour deposition from the reaction of aluminium salts with ammonia [11][12][13][14][15][16][17] and from organo-metallic precursors. [18][19][20] The preparation of an aluminium nitride thin film obtained from pulsed laser deposition (PLD) has been reported.…”
mentioning
confidence: 99%